Comparison between transthoracic echocardiography and transoesophageal echocardiography in the diagnosis of acute aortic dissection from an emergency perspective. A systematic review and meta-analysis - Zaki, Hany A.; Albaroudi, Bilal; Shaban, Eman E.; Alkahlout, Baha Hamdi; Yigit, Yavuz; Elnabawy, Wael; Basharat, Kaleem; Almarri, Nood Dhafi; Azad, Aftab Mohammad (Frontiers in Cardiovascular Medicine, 2024)
Background: Acute aortic dissection (AAD) is a life-threatening medical condition with high early fatality. Therefore, a prompt and precise diagnosis, which can be achieved through invasive and non-invasive techniques is vital. Echocardiography, unlike MRI and CT, is accessible in emergency units and bedside-compatible. The recommended echocardiographic techniques for AAD are transthoracic and transoesophageal echocardiography (TTE and TOE). Therefore, our review compares their diagnostic roles in AAD. Methods: Studies relevant to our topic were attained through a database search and manual scrutiny of references lists of articles obtained from the electronic databases. The Quality Assessment of Diagnostic Accuracy Studies tool (QUADAS-2) has been used for quality assessment. All quantitative analyses were performed using either STATA 16 or Comprehensive Meta-Analyst software. Results: The search strategy yielded 1798 articles, of which only 11 were eligible for inclusion. Our subgroup analysis showed that conventional TTE had a sensitivity and specificity of 85.35% and 84.51% for the diagnosis of Stanford type A AAD and was 45.89% sensitive and 87.05% specific for the diagnosis of type B AAD. However, the subgroup analysis shows that contrast-enhancement of TTE results in a sensitivity and specificity of 93.30% and 97.60% for diagnosis of type A AAD, and 83.60% and 94.50% for diagnosis of type B AAD, respectively. On the other hand, conventional TOE was 93.64% sensitive and 95.50% specific for the diagnosis of type A AAD, 99.80% sensitive and 99.87% specific for the diagnosis of type B AAD. Moreover, our analyses show that TTE has pooled false negative and positive rates of 28.6% and 18.6%, while TOE has shown false negative and positive rates of 2.4% and 4.3%, respectively. Conclusion: TOE is the more favorable diagnostic tool for AAD diagnosis than TTE. However, it cannot be used as a stand-alone diagnostic tool since misdiagnosis cases are being reported. Contrast-enhanced TTE can also diagnose AAD since it provides similar results to conventional TOE.